Surabaya Gempol Toll Road Towing and Patrol Car Service Application Using Android-Based GPS Tracker - Ahmad, Fikry; Mustafa, Lis Diana; Suharto, Nugroho (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
In today’s era of rapid development of information technology, transportation is one of the most important aspects of daily life so that traffic-free toll road infrastructure has been created. However, there are challenges in toll roads, namely the occurrence of accidents or complaints complained about by consumers on the toll roads that are passed. So this research will focus on serving toll road users who have an accident or have complaints by using an android application made for consumers to send complaints or request service assistance to the toll road. The service assistance offered by the toll road in the application is a tow truck and also a patrol car so that toll road users can choose one of the services offered. The purpose of this research is to facilitate users and determine the efficiency and productivity of towing car and patrol car services and assess the effectiveness of GPS tracker implementation on towing cars and patrol cars in tracking location and travel. The results of the gps tracker test show the gps accuracy rate of 86.85% so that the position of the gps tracker tool is still accurate. Then for the features contained in the application can run smoothly without any bugs or errors.